2017
DOI: 10.1111/jofi.12513
|View full text |Cite
|
Sign up to set email alerts
|

Volatility‐Managed Portfolios

Abstract: Managed portfolios that take less risk when volatility is high produce large alphas, increase Sharpe ratios, and produce large utility gains for mean‐variance investors. We document this for the market, value, momentum, profitability, return on equity, investment, and betting‐against‐beta factors, as well as the currency carry trade. Volatility timing increases Sharpe ratios because changes in volatility are not offset by proportional changes in expected returns. Our strategy is contrary to conventional wisdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
190
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(211 citation statements)
references
References 69 publications
13
190
1
1
Order By: Relevance
“…Additionally, as first proposed by Barroso and Santa‐Clara () and Moreira and Muir (), we use a simple risk estimate of the 1–0–1 strategy to scale the exposure to constant risk over time. For each month t , the variance forecasts σˆt2 are computed from daily returns in the previous month.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as first proposed by Barroso and Santa‐Clara () and Moreira and Muir (), we use a simple risk estimate of the 1–0–1 strategy to scale the exposure to constant risk over time. For each month t , the variance forecasts σˆt2 are computed from daily returns in the previous month.…”
Section: Methodsmentioning
confidence: 99%
“…However, the correlations between this proposed strategy and traditional industry momentum strategies are low, which is further supported by principal component analysis. Further analyses reveal that risk managing the zero-cost strategy in the spirit of Moreira and Muir (2017) adds value and substantially increases the Sharpe ratio. This finding supports that of Grobys, Ruotsalainen, and Äijö (2018) and Grobys (2018), who similarly document higher Sharpe ratios for risk-managed industry momentum strategies.…”
mentioning
confidence: 99%
“…For example,Moreira and Muir (2016) showed that a volatility-managed portfolio, which decreases portfolio volatility when the expected market risk is high and increases the portfolio volatility when expected market risk is low, yields high alphas and increases the portfolio Sharpe ratio significantly.…”
mentioning
confidence: 99%
“…Note that markettiming strategies are not necessarily doomed to fail and do not necessarily depend on a return chasing motif. In fact, according to the recent empirical and theoretical literature, if returns are somewhat predictable, then investors may be able to achieve higher Sharpe ratios by timing the market [see, Gallant et al (1990), Brandt (1999), Campbell and Viceira (2002) and Cochrane (2011)], for example, as a function of the current price to dividend ratio or market volatility (Moreira and Muir, 2017). Therefore, a priori, we cannot say if investors could do better than simply holding the market.…”
Section: Introductionmentioning
confidence: 99%